2004
DOI: 10.1038/sj.mp.4001412
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation and refinement of an ‘at-risk’ haplotype for schizophrenia suggests the EST cluster, Hs.97362, as a potential susceptibility gene at the Neuregulin-1 locus

Abstract: Two recent association studies have implicated the neuregulin-1 gene (NRG1) at chromosome 8p21-22 as a susceptibility gene for schizophrenia. Stefansson et al identified three 'at-risk' haplotypes (HapA, B and C) which spanned the NRG1 locus and shared a common core haplotype. Subsequently, they demonstrated evidence that the core haplotype was associated with schizophrenia in an independent Scottish sample. To confirm and refine this haplotype we investigated the NRG1 locus in an independent Irish case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
3
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 15 publications
(19 reference statements)
4
81
3
1
Order By: Relevance
“…These 'at-risk' haplotypes, all shared a common 'core' consisting of five SNPs and two microsatellite markers, the so-called Hap ICE , and extended a length of 290 kb from the 5 0 end of the GGF2 variant of the NRG1 and into the first exon of this splice form (see Figure 1). This finding was replicated in a follow-up study in a Scottish population, 23 and a succession of replication studies in additional populations ensued, including studies in a number of Chinese populations, [24][25][26] an Irish population, 27 a population from the British Isles, 28 and a Portuguese population. 29,30 However, neither these nor the original study have identified the putative disease-causing variant within NRG1.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…These 'at-risk' haplotypes, all shared a common 'core' consisting of five SNPs and two microsatellite markers, the so-called Hap ICE , and extended a length of 290 kb from the 5 0 end of the GGF2 variant of the NRG1 and into the first exon of this splice form (see Figure 1). This finding was replicated in a follow-up study in a Scottish population, 23 and a succession of replication studies in additional populations ensued, including studies in a number of Chinese populations, [24][25][26] an Irish population, 27 a population from the British Isles, 28 and a Portuguese population. 29,30 However, neither these nor the original study have identified the putative disease-causing variant within NRG1.…”
Section: Introductionmentioning
confidence: 75%
“…9,[23][24][25][26][27][28][29]52 Two of the five SNPs defining the at-risk haplotype previously reported 9 were included in this study, SNPnrg2 and SNPnrg4. These two SNPs plus three additional ones typed in this study were located in the area of Hap ICE .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45][46][47][48][49] In schizophrenia patient brain samples, markers of GABAergic neurons are reduced in expression and postsynaptic receptor complexes are increased in number. 47,50,51 Furthermore, there is evidence that neuregulin 1 (NRG1) and dysbindin (DTNBP1), two schizophrenia candidate risk genes, 33,[52][53][54][55][56][57][58][59][60][61][62][63][64][65] interact with the GABA A receptor. For example, treatment of the rat hippocampus with NRG1 resulted in lower expression of GABA A receptor subunit transcripts, 66 while dysbindin likely colocalizes with GABA A receptor subunits in the hippocampus, cortex, and cerebellum through its association with beta-dystrobrevin in the dystrophin protein complex.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this marker was selected based on its presence within an Irish schizophrenia-associated haplotype, HapB IRE . 7 A range of two to three marker haplotypes, including HAP ICE and HapB IRE , also failed to exhibit any evidence of association with BPAD (Table 1). A haplotype comprised of alleles from the three microsatellite markers (M3-M4-M5) did exhibit a marginal association (Table 1, haplotype 1, 3, 5, uncorrected P = 0.04) which was not significant at the global haplotype level (Table 1: P = 0.31).…”
mentioning
confidence: 97%